Design of the BiRmingham Early Detection In untREated psyChosis Trial (REDIRECT): cluster randomised controlled trial of general practitioner education in detection of first episode psychosis [ISRCTN87898421] - Freemantle Nick; Birchwood Max; Lester Helen; Tait Lynda; Wilson Sue (BMC, 2005)
Abstract Background Treatment delay in first episode psychosis is common. As general practitioners are the first point of contact for many individuals with first episode psychosis, they are well placed to detect the early symptoms and make urgent referrals to specialist secondary care services. However, early psychosis is often difficult to detect. The primary objective of the Redirect trial is to estimate whether an educational intervention targeted at general practitioners increases the general practitioner referral rate of young people with first episode psychosis to Early Intervention Services. Methods/design This paper describes the design of a stratified-cluster randomised controlled trial of an educational intervention on first episode psychosis in primary care. The primary outcome is the number of general practitioner referrals of young people with first episode psychosis to Early Intervention Services. Secondary outcomes are duration of untreated psychosis, time to recovery, use of the Mental Health Act, and general practitioner consultation rate. Young people with first episode psychosis referred to Early Intervention Services will be recruited over a two-year period from 1 March 2004. Seventy-eight out of 89 eligible general practices were recruited. The educational intervention has been implemented and evaluated by general practitioners. The education was well received and considered relevant to clinical practice by the general practitioners. Discussion The results suggest that the recruitment strategy and implementation of the educational intervention are feasible and acceptable in a primary care setting. The Redirect trial will provide robust information about the efficacy of an evidence-based complex educational intervention targeted at general practitioners on referral rates of young people with first episode psychosis to Early Intervention Services.